2004
DOI: 10.1118/1.1668393
|View full text |Cite
|
Sign up to set email alerts
|

Accurate determination of dose‐point‐kernel functions close to the origin using Monte Carlo simulations

Abstract: Dose-point-kernel (DPK) functions are used extensively for the dosimetry of gamma and beta emitters in many physical problems. These functions are usually obtained from Monte Carlo simulations where the energy deposited in concentric spherical shells around a point source is tallied. The energy scored in a spherical shell divided by the shell mass is taken as the dose at some effective radius R(eff) of the shell. The effective radius R(eff), defined as the distance of a hypothetical zero-thickness scoring regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…The emission of the primary monoenergetic electrons or photons was uniformly and isotropically distributed within the central voxel, (0,0,0), while the energy deposition in the voxels was averaged over the eight octants of the 3D space, for symmetry reasons. Each voxel is identified by (i,j,k) indexes ranging from (−5,−5,−5) to (5,5,5).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The emission of the primary monoenergetic electrons or photons was uniformly and isotropically distributed within the central voxel, (0,0,0), while the energy deposition in the voxels was averaged over the eight octants of the 3D space, for symmetry reasons. Each voxel is identified by (i,j,k) indexes ranging from (−5,−5,−5) to (5,5,5).…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, the convolution of precalculated electron and photon dose point-kernels with the voxelized spatial distribution of activity has been employed for threedimensional dosimetry in uniform media; 3,4 electron and photon dose point-kernels have been calculated, mainly in water, through the various Monte Carlo codes available, [5][6][7] and approximated analytical models were proposed in order to simplify the convolution algorithms. [8][9][10] The voxel S values (VSVs) approach, introduced in 1999 by the MIRD Committee, 11 has been used more widely than dose point-kernel and direct Monte Carlo computation approaches, due to its recognized simplicity and reliability.…”
Section: Introductionmentioning
confidence: 99%
“…Radiation transport simulations performed with a spherical shell model (e.g., Janicki and Seuntjens, 2004) can be used to calculate, for a sphere containing a uniform distribution of sources, the radial dependence of dose within the sphere and extending into the surrounding medium ( Fig. SM4) which is related to the DPK, F(s).…”
Section: Sm3 Spherical Source -Dose Profilementioning
confidence: 99%
“…29 Other studies about short range accuracy and voxel based kernels have been reported. 30,31 These studies will be important for the wide use of the dose point kernel method for performance of microdosimetry.…”
Section: Dose Point Kernel and Monte Carlo Simulationmentioning
confidence: 99%